THE WHATS, WHYS, HOWS AND WHOS OF CONTENT-BASED INSTRUCTION IN SECOND/FOREIGN LANGUAGE EDUCATION - Dueñas, María (International Journal of English Studies, 2009)
As an instructional practice in second and foreign language education, content-based instruction is not a fully revolutionary paradigm, but a spin-off approach which derives from the evolution of Communicative Language Teaching. Sharing with CLT the same fundamental principies, CBI bases its idiosyncrasy on promoting the use of subject matter for secondlforeign language teaching purposes. This article aims at exploring the nature and scope of the content-based methodological framework -the whats-, the theoretical foundations that support it -the whys-, and the different prototype models for application in compliance with parameters such as institutional requirements, educational leve], and the particular nature and object of instruction -the hows. Additionally, it will also undertake a review of a copious nurnber of references selected from the existing literature, mostly contributed by researchers and experienced practitioners in the field -the whos.